2010
DOI: 10.1186/1477-7517-7-29
|View full text |Cite
|
Sign up to set email alerts
|

Opioid substitution therapy in manipur and nagaland, north-east india: operational research in action

Abstract: BackgroundThere is good evidence for the effectiveness of opioid substitution therapy (OST) for injecting drug users (IDUs) in middle and high-income countries but little evidence regarding the provision of OST by non-government organisations (NGOs) in resource-poor settings. This paper reports on outcomes of an NGO-based OST program providing sub-lingual buprenorphine to opiate dependent IDUs in two north-east Indian states (Manipur and Nagaland), a region where conflict, under-development and injecting of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…15 The retention rate of clients in the opioid substitution treatment programme after 6 months is 63%. 14,16 Between 2009 and 2011, the percentage of registered programme participants who had been injecting opioids for less than one year increased from 4% (146) to 21.5% (1071), and the fraction of females registered at the programme increased from 2.7% (119) to 7% (340). Between 2010 and 2012, the fraction of females injecting opioids who were contacted monthly increased from 69% (104) to 100% (150) and monthly tests for HIV increased from 3% (5) to 8% (12) Safe injecting behaviour, already frequent among people injecting opioids (i.e.…”
Section: Programme Scale and Scopementioning
confidence: 99%
“…15 The retention rate of clients in the opioid substitution treatment programme after 6 months is 63%. 14,16 Between 2009 and 2011, the percentage of registered programme participants who had been injecting opioids for less than one year increased from 4% (146) to 21.5% (1071), and the fraction of females registered at the programme increased from 2.7% (119) to 7% (340). Between 2010 and 2012, the fraction of females injecting opioids who were contacted monthly increased from 69% (104) to 100% (150) and monthly tests for HIV increased from 3% (5) to 8% (12) Safe injecting behaviour, already frequent among people injecting opioids (i.e.…”
Section: Programme Scale and Scopementioning
confidence: 99%
“…Following two successful pilots in 1999-2002 12 and 2006-07, 11 the National AIDS Control Organization has included opioid substitution therapy in its third five-year plan, proposing to scale-up the programme to reach 40 000 injecting drug users by 2011. 13 However, coverage remains inadequate at this time and challenges to the scale-up include: current unavailability of methadone (but not of buprenorphine, a more costly alternative); ineffective health services in some areas, necessitating government accreditation and monitoring of many existing opioid substitution therapy programmes run by nongovernmental organizations; and residual scepticism about its value in India.…”
mentioning
confidence: 99%
“…Study conducted by Armstrong et al revealed that 47.3% and 44.8% were single among the IDUs in Manipur and Nagaland, respectively. [11] Separated or divorced IDUs were found to be 3.6% and 3.2% in the above mentioned two northeastern states, respectively. [11] In our study, 36% percent IDUs were illiterate whereas only 8.8% of the study participants studied up to secondary level and above (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[11] Separated or divorced IDUs were found to be 3.6% and 3.2% in the above mentioned two northeastern states, respectively. [11] In our study, 36% percent IDUs were illiterate whereas only 8.8% of the study participants studied up to secondary level and above (Table 1). Razzaghi et al in his study in Tehran showed that out of the 154 IDUs who had participated in the study, 18.7% were either illiterate or were barely able to read and write while only 10.7% had graduated from high school or had higher education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation